Red or Expert? The Anglo–Soviet Exchange of Ambassadors in 1929. Issue 3 (2nd July 2016) - Bridges, Brian
ABSTRACT: Throughout the 1920s, distrust and contention marked Anglo–Soviet relations, culminating in the diplomatic break in 1927. In 1929, the incoming Labour government successfully pursued its objective of re-establishing diplomatic relations with Moscow, but the follow-up in terms of ambassadorial appointments was far from routine for either side. This analysis shows that internal pressures complicated decisions about whether to appoint career diplomats or choose political figures. Resisting both claims from enthusiastically hopeful Labour backbenchers and criticisms from the left wing media, the British foreign secretary, Arthur Henderson, chose a Russian-speaking career diplomat. On the Soviet side, the first choice was a controversial politician, but then replaced by a financial expert, albeit one tainted as a defeated political opponent of Josef Stalin. Whilst both ambassadors could be considered "professionals, " neither was able to have a deep impact on the relationship, which remained troubled.